Effects Of Beneficial Diazotrophs On Growth Of Seedlings And Tissue-Cultured Plantlets Of Oil Palm (Elaeis Guineensis Jacq.) - Othman, Noor Ai’shah (2010)

(untitled)
The agricultural sector in Malaysia is moving towards environmentally sustainable practices. Biological Nitrogen Fixation (BNF) process can be adopted to minimize the usage of inorganic N fertilizer. The biological nitrogen fixation process occurred when the diazotrophs are inoculated to the agricultural crop and establish beneficial symbiotic or non-symbiotic relationships with the host plants. The interaction between plant and diazotrophs would also influence synthesis of phytohormone (indole-3-acetic acid). Generally, IAA excreted by the bacteria would increase top and root biomass and lateral root numbers of the host plants. Thus, combination of both BNF and synthesis of phytohormones of the diazotrophs would finally improve yield of the host plants. Therefore, the beneficial diazotrophs have the potential to be introduced to tissue cultured oil palm under in vitro and glasshouse conditions.